Efektivitas Pembelajaran Fisika Berbasis Multirepresentasi pada Materi Momentum dan Impuls untuk Meningkatkan Keterampilan Pemecahan Masalah (UPEJ Unnes Physics Education Journal, 2022)
Each student has different specific abilities. Differences in the specific abilities of each learner are taken into consideration in choosing a learning model. The presentation of physical concepts and phenomena in various representations makes learners understand the concept more thoroughly and fully. The research aims to improve students' problem-solving skills on momentum and impulse materials. It is hoped that this research can provide input on learning models used in aligning physical matter. The research method used is Quasi Experimental design using Nonequivalent Control Groub Design. Momentum and impulse materials are taught with multirepresentation-based learning in experimental classes and conventional learning models in control classes. The results showed an increase in students' problem-solving skills in experimental classes where n-gain was 0.50 with moderate categories and in n-gain control classes by 0.16 with low categories. t test for problem-solving skills yielding value 2,785 which is greater than the . The effectiveness of learning was 73.6% in experimental classes that fall into the effective category. Based on the results of data analysis states that multirepresentation-based physics learning when aligning momentum and impulse materials can improve problem-solving skills in students and multirepresentation-based physics learning is effectively used to teach momentum and impulse materials.